SARS-CoV-2-induced Host Metabolic Reprogram (HMR): Nutritional Interventions for Global Management of COVID-19 and Post-Acute Sequelae of COVID-19 (PASC) - A. Satyanarayan Naidu; Fereidoon Shahidi; Chin-Kun Wang; Kenji Sato; Aman Wirakartakusumah; Ogugua C. Aworhf; Barry Halliwell; Roger A. Clemensh (Journal of Food Bioactives, 2022)
‘Severe acute respiratory syndrome coronavirus 2’ (SARS-CoV-2) is a highly transmissible viral pathogen responsible for the ongoing ‘coronavirus disease 2019’ (COVID-19) pandemic.  The current re-purposed antiviral interventions against SARS-CoV-2 are classified into two major groups: Group-1 represents the family of drugs, mainly the vaccines that directly target the virus, and Group-2 includes a specific class of inhibitors that interfere with the host-cell machinery, which is critical for viral infection and replication.  Global efforts to control COVID-19 pandemic with vaccines and repurposed therapeutics represent only a phased victory.  The emergence of several SARS-CoV-2 variants of concern (VOCs) has compromised several vaccinations and pharma-therapeutic protocols, which highlights the dire necessity for specific antiviral interventions that target highly conserved domains, which are less likely to mutate in the SARS-CoV-2 genome.  Several bioactive phytochemicals that block viral enzymes such as nsp5/main proteinase (Mpro) and RNA-dependent nsp7/nsp8/nsp12 RNA-dependent RNA-polymerase (RdRp) complex, are extensively investigated in this direction.  The SARS-CoV-2 infection triggers a complex human host-pathogen interaction(s) resulting in ‘host metabolic reprogramming’ (HMR), iron (Fe)-redox dysregulation (FeRD), and altered mitochondrial function that cumulatively disrupt several metabolic pathways involved in cellular energy and antioxidant enzyme function; thereby, compromise the innate host defense.  The circulatory/RAAS axis contributes to FeRD and any alteration or imbalance in the Fe-redox homeostasis (Fe-R-H) may lead to ‘new onset’ metabolic disorders (i.e., diabetes).  Such inherent body damage and its long-term health consequences in post-acute sequelae of COVID-19 (PASC) require effective nutritional intervention strategies, particularly at the interface of organ system functions and immune system dynamics.  The long-term sequelae of PASC indicate an accelerated rate of immune exhaustion in COVID-19 patients, due to prolonged antigen stimulation (also due to vaccine exposure).  Abnormal immune metabolism may also cause systemic perturbations (i.e., FeRD), ROS/RNS production, oxidative and nitrosative stress, which could trigger multi-organ disorders ranging from mild symptoms to an incapacitating state and reduced quality of life that could last for weeks or longer following recovery from COVID-19.  The five most long-term clinical manifestations of PASC include fatigue, headache, attention disorder, hair loss, and dyspnea.  This narrative review elucidates the intricate impairments and sequelae associated with eight major physiological systems in COVID-19 survivors (i.e., pulmonary, neuro-cognitive, cardiovascular, renal, gastrointestinal/hepato-biliary, endocrinal, skeleton-muscular, and reproductive) – triggered by the FeRD, amplified by the HMR, altered mitochondrial function and ACE2/RAAS axis.  We have attempted to explain the ongoing epidemic of the residual, non-viral host metabolic disorders and complications in COVID-19 survivors and the supportive role of specific host system-targeted nutritional interventions such as natural plant-based anti-inflammatories, immune-modulators, antioxidants, and macro-/micronutrient metabolic optimizers to manage PASC, the newly emerged post-COVID metabolic syndrome.